Soluble P‐tau217 reflects amyloid and tau pathology and mediates the association of amyloid with tau - Niklas Mattsson‐Carlgren; Shorena Janelidze; Randall J Bateman; Ruben Smith; Erik Stomrud; Geidy E Serrano; Eric M Reiman; Sebastian Palmqvist; Jeffrey L Dage; Thomas G Beach; Oskar Hansson (EMBO Molecular Medicine, 2021)
Abstract Alzheimer’s disease is characterized by β‐amyloid plaques and tau tangles. Plasma levels of phospho‐tau217 (P‐tau217) accurately differentiate Alzheimer’s disease dementia from other dementias, but it is unclear to what degree this reflects β‐amyloid plaque accumulation, tau tangle accumulation, or both. In a cohort with post‐mortem neuropathological data (N = 88), both plaque and tangle density contributed independently to higher P‐tau217, but P‐tau217 was not elevated in patients with non‐Alzheimer’s disease tauopathies (N = 9). Several findings were replicated in a cohort with PET imaging (“BioFINDER‐2”, N = 426), where β‐amyloid and tau PET were independently associated with P‐tau217. P‐tau217 concentrations correlated with β‐amyloid PET (but not tau PET) in early disease stages and with both β‐amyloid and (more strongly) tau PET in late disease stages. Finally, P‐tau217 mediated the association between β‐amyloid and tau in both cohorts, especially for tau outside of the medial temporal lobe. These findings support the hypothesis that plasma P‐tau217 concentration is increased by both β‐amyloid plaques and tau tangles and is congruent with the hypothesis that P‐tau is involved in β‐amyloid‐dependent formation of neocortical tau tangles.